Sustainable Tourism: Analysis of the AISAS Model Through Instagram Social Media @TRAVELXISM During Voluntrip Activities - Salsabila, Elvira; Jailani, Muhammad; Ali, Muhammad (Pencerah, 2025)
Instagram account @Travelxism focuses on travel and exploration of tourist destinations, aims to integrate a social media management approach that focuses on sustainable tourism through Voluntrip activity content, this Instagram account aims to make its followers more aware of sustainable tourism and encourage actions that support the principles of sustainable tourism The purpose of this study is to analyze the extent to which the use of the Travelxism Instagram account in Voluntrip Activities and the strategies used in developing sustainable tourism This research is qualitative using secondary data through a review of the literature review of the general description of marketing communication strategies through the Instagram account